Early multimodal rehabilitation following lumbar disc surgery: a randomised clinical trial comparing the effects of two exercise programmes on clinical outcome and lumbar multifidus muscle function. Issue 2 (12th September 2013) - Hebert, Jeffrey J; Fritz, Julie M; Thackeray, Anne; Koppenhaver, Shane L; Teyhen, Deydre
Abstract : Background: The optimal components of postoperative exercise programmes following single-level lumbar discectomy have not been identified. Facilitating lumbar multifidus (LM) function after discectomy may improve postoperative recovery. The aim of this study was to compare the clinical and muscle function outcomes of patients randomised to receive early multimodal rehabilitation following lumbar discectomy consisting of exercises targeting specific trunk muscles including the LM or general trunk exercises. Methods: We included participants aged 18 to 60 years who were scheduled to undergo single-level lumbar discectomy. After two postoperative weeks, participants were randomly assigned to receive an 8-week multimodal exercise programme including either general or specific trunk exercises. The primary outcome was pain-related disability (Oswestry Index). Secondary outcomes included low back and leg pain intensity (0–10 numeric pain rating scale), global change, sciatica frequency, sciatica bothersomeness and LM function measured with real-time ultrasound imaging. Treatment effects 10 weeks and 6 months after surgery were estimated with linear mixed models. Results: 61 participants were randomised to receive a general trunk (n=32) or specific (n=29) exercise programme. There were no between-group differences in clinical or muscle function outcomes. Participants in both groups experienced improvements in most outcome measures. Conclusions: Following lumbar discectomy, multimodal rehabilitation programmes comprising specific or general trunk exercises have similar effects on clinical and muscle function outcomes. Local factors such as the individual patient characteristics identified by specific assessment findings, clinician expertise and patient preferences should direct therapy selection when considering the types of exercises tested in this trial for inclusion in rehabilitation programmes following lumbar disc surgery.